Territorial Impact Assessment: Cohesion policy and balanced territorial development (Czechia) - Jiří Novosák; Oldřich Hájek; Lucie Severová; Daniela Spiesová; Jana Novosáková (DETUROPE)
The intent of this paper is to add to the current knowledge in the field of TIA modelling by presenting a case study of cohesion policy (CP) in Czechia, 2007-2013. The empirical results are mixed. While the territorial impact of CP interventions concerning the NSRF objective of a 'Competitive Czech Economy' is higher in main metropolitan regions, CP interventions concerning the NSRF objectives of an 'Open, Flexible and Cohesive Society' and of an 'Attractive Environment' have higher impacts in regions with more desire for CP interventions. Consequently, territorial impacts of the three NSRF objectives are contrary to one another, and the observed pattern of overall territorial impacts of CP interventions is patchy, almost mosaic-like. Additionally, the paper suggests some methodological ideas for TIA modelling drawing inspirations from the prominent TEQUILA model. In particular, the spatial distribution of SF is used to model the intensity of CP interventions in a territory. A methodology how to model the potential territorial impact and the desirability of CP interventions in a territory is also presented.